Hubungan Durasi QRS Awal Dengan Derajat Reperfusi Miokard Setelah Angioplasti Koroner Perkutan Primer - Andre P Ketaren; Ganesja M Harimurti; Ismoyo Sunu (The Indonesian Heart Association, 2009)
Background.Reperfusion therapy in acute myocardial infarction aims at early and sustained reperfusion of the myocardium at risk. However, even when TIMI flow 3 is achieved, some patients have less optimal reperfusion at myocardial tissue level. QRS duration before reperfusion therapy was showed as a predictor of myocardial reperfusion after fibrinolytic therapy, but currently there is no data showing relationship between QRS dura-tion at admission with myocardial reperfusion after primary percutaneous coronary intervention (primary PCI).Methods.A case control study was conducted to study the relationship between QRS duration at admission with myocardial reperfusion after pri-mary PCI. Myocardial reperfusion was assessed by myocardial blush grade (MBG), and was grouped as optimal reperfusion (MBG 2-3) and impaired reperfusion (MBG 0-1).Results.There were 41 patients fulfilling study criteria. Thirty one patients had optimal reperfusion and 10 patients had impaired reperfusion. Impaired reperfusion group had longer QRS duration (103 +14 vs 91 +12 ms; p = 0,013) and were older (63,9 +12,2 vs 53,7 +10,3 years, p = 0,023). The two groups were similar in terms of gender, diabetes, hypertension, dyslipidemia, smoking status, pain-to-door time, pain-to-balloon time, infarct-related artery location, and TIMI flow. Multivariate analysis showed that longer QRS duration was associated with impaired reperfusion after primary PCI (OR: 21.7, p = 0.014). QRS duration of more than 105 ms was a predictor of impaired reperfusion after primary PCI, with 84% sensitivity and 62% specificity.Conclusions.Longer QRS duration at admission is a predictor of impaired myocardial reperfusion after primary PCI. Patients with STEMI who have QRS duration of more than 105 ms should be considered to be at higher risk of impaired reperfusion after primary PCI.